Dobrushin's approach to queueing network theory. (1996) - Karpelevich, F. I.; Pechersky, E. A.; Suhov, Yu. M.
Abstract : R.L. Dobrushin (1929-1995) made substantial contributions to Queueing Network Theory (QNT). A review of results from QNT which arose from his ideas or were connected to him in other ways is given. We also comment on various related open problems.